2016
DOI: 10.1136/thoraxjnl-2015-208054
|View full text |Cite
|
Sign up to set email alerts
|

The short-term association between asthma hospitalisations, ambient temperature, other meteorological factors and air pollutants in Hong Kong: a time-series study

Abstract: People with asthma should avoid exposure to adverse conditions by limiting outdoor activities during periods of extreme temperatures, combinations of high humidity and high temperature, and low humidity and low temperature, and high ozone levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
130
1
15

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(168 citation statements)
references
References 47 publications
7
130
1
15
Order By: Relevance
“…Numerous time-series and case-crossover studies have reported that short-term exposure to both cold and hot temperatures were associated with increased risks of respiratory mortality10 and hospital admissions 11. Most of those studies focused on the adverse health effects of short-term mean temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous time-series and case-crossover studies have reported that short-term exposure to both cold and hot temperatures were associated with increased risks of respiratory mortality10 and hospital admissions 11. Most of those studies focused on the adverse health effects of short-term mean temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Asthmatics are at especially high risk for ozone-induced respiratory complications due to their heightened inflammatory and bronchoconstrictive responses (Peden et al 1997). Consequently, asthma-related emergency department visits and hospitalizations increase significantly 1-3 days after high ozone days (Mar and Koenig 2009;Gleason et al 2014;Sheffield et al 2015;Lam et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The 2006 California heat wave was linked with increased risk of admission for acute renal failure, electrolyte imbalance, and nephritis (Knowlton et al 2009). Time series studies of heat and hospitalizations without focus on a particular heat event have found associations between heat and hospitalization for various respiratory, cardiovascular and renal conditions (Isaksen et al 2015; Lam et al 2016; Li et al 2015; Soneja et al 2016). A study of heat, heat waves, and hospitalizations among the elderly in 114 cities across the U.S. found associations between renal and respiratory hospitalizations and EH.…”
Section: Introductionmentioning
confidence: 99%